Translanguaging and Its Role in Enhancing Comprehension among Fifth-Semester English Literature Students at USU - Ndruru, Mesra Hati; Arifa, Najwa; Surbakti, Sara Jesika; Yacub, Muhammad Arifandi; Tumanggor, Hadlinten Josua (Universitas Pamulang, 2026)
This study investigates the role of translanguaging in enhancing comprehension among fifth-semester English Literature students in Class B at Universitas Sumatera Utara. The research addresses the difficulties students face when engaging with complex literary and theoretical texts in a foreign language learning environment. The primary purpose of this study is to examine how translanguaging practices, understood as the flexible and purposeful use of multiple linguistic resources, support students’ understanding, interpretation, and participation in classroom activities. Employing a qualitative descriptive design, the study collected data through classroom observations, semi-structured interviews, and document analysis of students’ learning artifacts. The analysis focused on identifying patterns of translanguaging use and examining their impact on students’ comprehension processes. The results show that translanguaging plays a significant role in helping students connect their prior linguistic knowledge with academic English, enabling them to grasp abstract concepts and interpret texts more effectively. Students were observed using translanguaging strategically to clarify meanings, negotiate interpretations, and scaffold their peers’ understanding. Furthermore, translanguaging reduced language anxiety, minimized gaps in English proficiency, and encouraged a more collaborative and inclusive learning environment. These practices ultimately supported deeper engagement with course materials and enhanced overall comprehension. The findings indicate that translanguaging can serve as an effective pedagogical approach in higher education literature courses, particularly in multilingual contexts such as Indonesia. This study contributes to the discourse on multilingual pedagogy and offers practical insights for educators seeking to integrate translanguaging as a dynamic strategy to strengthen learning outcomes in English Literature programs.